49 ESTROGEN MODULATES NEUTROPHIL CHEMOTAXIS ACTIVITY OF RAT AORTIC SMOOTH MUSCLE CELLS TREATED WITH TUMOR NECROSIS FACTOR α. (1st January 2005) - Xing, D.; Feng, W.; Weathington, N. M.; Chen, Y. F.; Blalock, E. J.; Oparil, S.
Abstract : Introduction: Inflammation plays an important role in pathogenesis of vascular disease. Estrogen (17β-estradiol, E2) negatively modulates neointima formation in response to vascular injury, in part by attenuating expression of pro-inflammatory mediators and migration of leukocytes (primarily neutrophils and monocyte/macrophages) into injured vessels. Cytokine-induced neutrophil chemoattractant (CINC)-2 is a potent chemokine that causes neutrophil recruitment and provokes neutrophil activation in vitro. This study tested the hypothesis that activated rat aortic smooth muscle cells (RASMC) express CINC-2 and induce neutrophil migration in vitro, and that E2 inhibits these processes by an estrogen receptor (ER) dependent mechanism. Methods: Quiescent cultured RASMCs were pretreated with E2 or vehicle for 24 hours before tumor necrosis factor (TNF)-α was added. After 6 hours of treatment, total RNA was extracted from cells using TRIzol reagent, and SYBR green real-time RT-PCR was used to detect expression of CINC-2 mRNA. Conditioned media was collected and concentrated to measure CINC-2 protein level by ELISA. To assess neutrophil chemotactic activity of conditioned media, in vitro chemotaxis assays were performed using differentiated HL-60 cells in a 96-well modified Boyden chamber appropriate for the evaluation of leukocyte chemotaxis. The nonselective ER antagonist ICI-182780 was given to cells 2 hours prior to E2 incubation to study the mechanism of E2 effect. Results: Steady state of CINC-2 mRNA was undetectable in unstimulated RASMCs; TNF-α (0.1 ng/mL to 2.5 ng/mL) dose dependently stimulated CINC-2 mRNA expression, and E2 pretreatment significantly reduced TNF-α-stimulated CINC-2 expression (by 30%). ICI-182780 completely blocked the E2 effect, indicating ER dependence. ELISA confirmed increased of CINC-2 protein in conditioned media from RASMCs stimulated with TNF-α and E2-induced inhibition of CINC-2 expression. Conditioned media from RASMCs treated with TNF-α produced a 2-fold increase in migration of differentiated HL-60 cells compared to conditioned media from vehicle treated cells. E2 treatment markedly inhibited this effect. Conclusion: This study suggested that the vasoprotective effects of E2 in injured arteries may be mediated, at least in part, by an inhibitory effect on expression of the neutrophil chemoattactant CINC-2 in injured arterial SMCs, with resultant attenuation of neutrophil infiltration and inflammatory damage to the blood vessel.